Proposta de ensino de filosofia hipermidiático : da teoria à prática - Jobim, Andrews Dubois (2023)
The ways of updating philosophy teaching have been discussed for a long time, seeking to bring it closer to the contemporary trends of young students. However, there were only significant pedagogical innovations or advances at the beginning of the COVID-19 pandemic period to make it possible for school activities to continue. Thus, teaching started to be mediated by computers or cell phones through videoconferencing tools and other interactive resources, proving that it is possible to implement new ways of teaching. It is urgent to continue researching the integration of digital technologies and the teaching of philosophy, to give subsidies to teachers who want to innovate their practices and prevent, once the pandemic situation is over, the old classroom practices will become dominant again. Thus, this investigation focuses on this integration, thinking not only theoretically but also in practice through constructing an educational artifact aimed at the real classroom context. For this, it uses the Design-Based Research methodology, characterized by its pragmatic, iterative, and contextual character, to cover the complexity of responding to the problems that arise. Two philosophy professors are participating in this study, acting as co-creators, discussing and elaborating with the researcher the product of this research in two application cycles. As a result, a conceptual triangulation between Gilles Deleuze and Félix Guattari, Piérre Lévy, and Silvio Gallo constituting a conceptual apparatus to be appropriated by teachers, as well as a pedagogical proposal that proposes the targeted integration, serving as a practical example. We suggest design principles that can guide new implementations of the integration between digital technologies and philosophy teaching. The term “hypermedia philosophy teaching” results from synthesizing this effort to integrate digital technologies into philosophy teaching.